The Impact of Merger and Acquisition on the Profitability of Medium Sized Technology Companies Listed on New York Stock Exchange (Journal of Academic Finance, 2021)
Objective: The purpose of the study is to identify the influence of merger and acquisition on the technology companies’ profitability.Method: Therefore, the five medium-sized technology companies, listed on New York Stock Exchange, and profitability ratios, including return on assets, return on equity, and earnings per share, have been selected. The Independent sample T-test is used for this study. The financial data that has been gathered from the U.S. Securities and Exchange Commission, companies’ annual reports, and NASDAQ website over the period from 2003 to 2020.Results: The results indicate that the earnings per share ratio increased while both returns on assets and return on equity ratios deteriorated. However, the earnings per share ratio significantly improved and the return on equity significantly declined while there was no significant impact on return on assets. The study concludes that the overall profitability decreased whereas the earnings per share faced a significant rise and return on equity ratios was found to be decreased significantly.Originality / Relevance: This study is one of the few studies which have evaluated the effect of the merger and acquisition on the profitability of medium-sized technology companies listed on New York Stock Exchange, over the period from 2003 to 2020.Theoretical/methodological contributions: The paper contributes to the existing literature on merger and acquisition by providing empirical evidence of the impact of merger and acquisition on profitability.Social/management contributions: This study will help technology investors and investment management companies to make investment decisions, and can also be helpful for the acquirer companies to handle the consequences of the merger on profitability.
Keywords: Profitability, return on assets, return on equity, earnings per share, Technology companies, New York Stock Exchange, Merger and acquisition